Pelatihan Pemanfaatan Perangkat Lunak PhET bagi Guru IPA Dan Matematika di SDIT Nuur A’laa Nuur Tambun Bekasi dalam Membentuk Pembelajaran yang Kreatif dan Inovatif - Muthi’ah Alfiyah Yamin; Diyan Parwatiningtyas; Dinda Rahma Dewi; M. Zuhnir Piliang (Indonesian Journal of Emerging Trends in Community Empowerment, 2023)
Training on the use of PhET software for science and mathematics teachers at SDIT Nuur A'laa Nuur Tambun Bekasi Selatan aims to provide knowledge about the use of interactive PhET simulations in learning science and mathematics. The stages in the training start from the stages of planning, preparation, implementation, and ending with the evaluation stage. The method of carrying out this training is the method of presentation, demonstration, question and answer, and games using Quizizz Software. The results of this training showed that 70% of the participants understood how to use PhET in learning science and mathematics well. This training is expected to help teachers implement PhET in creative and innovative learning.